How do mortgage refinances affect debt, default, and spending? Evidence from HARP - Joshua Abel; Andreas Fuster (Federal Reserve Bank of New York, 2018)
We use quasi-random access to the Home Affordable Refinance Program (HARP) to identify the causal effect of refinancing a mortgage on borrower balance sheet outcomes. We find that on average, refinancing into a lower-rate mortgage reduced borrowers' default rates on mortgages and nonmortgage debts by about 40 percent and 25 percent, respectively. Refinancing also caused borrowers to expand their use of debt instruments, such as auto loans, home equity lines of credit (HELOCs), and other consumer debts that are proxies for spending. All told, refinancing led to a net increase in debt equal to about 20 percent of the savings on mortgage payments. This number combines increases (new debts) of about 60 percent of the mortgage savings and decreases (paydowns) of about 40 percent of those savings. Borrowers with low FICO scores or low levels of unused revolving credit grow their auto and HELOC debt more strongly after a refinance but also reduce their bank card balances by more. Finally, we show that take-up of the refinancing opportunity was strongest among borrowers that were in a relatively better financial position to begin with.
Keywords: D14; E21; G21; 330; mortgages; refinancing; monetary policy transmission; heterogeneity; HARP